Interaction of epsilon-globin cis-acting control elements with erythroid-specific regulatory macromolecules. - Wu, J (1990)
We have used a competition assay to investigate the influence of erythroid-specific cellular factors on transcription from the human epsilon-globin major cap site promoter and the minor promoter located 200 base pairs (bp) upstream from the epsilon-globin cap site. In the human erythroid cell line K562, competition of the epsilon-globin major cap site promoter linked to the chloramphenicol acetyltransferase (CAT) gene (epsilon P-CAT) with the same promoter fragment linked to a neomycin resistance gene (epsilon P-NEO) leads to a reduction in CAT activity. This indicates the specific presence of K562 cells of factor(s) which interact with the 200-bp promoter fragment (isolated from the gene body or flanking sequences) to activate transcription from the epsilon-globin major cap site. Competition of the epsilon-globin major promoter (as epsilon P-CAT) with the upstream minor epsilon-globin promoter (as epsilon P2-NEO) also leads to a reduction in CAT activity, indicating that both promoters share erythroid-specific trans-acting factors. The reverse competition (epsilon P2-CAT with epsilon P-NEO) leads to an increase in CAT activity, suggesting that the existence of erythroid-specific factor(s) which repress transcription from the 200-bp-upstream epsilon-globin promoter.